2002
DOI: 10.1046/j.1365-2141.2003.04040.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein‐1 alpha is produced by human multiple myeloma (MM) cells and its expression correlates with bone lesions in patients with MM

Abstract: Summary. Macrophage inflammatory protein-1 alpha (MIP-1a) is a chemokine primarily associated with bone absorption. We examined whether MIP-1a was produced by purified fresh tumour cells isolated from bone marrow samples from 31 multiple myeloma (MM) patients. High levels of MIP-1a were found in supernatants of myeloma cell cultures. Immunohistochemical staining showed MIP-1a in the cytoplasm of myeloma cells. MIP-1a mRNA expression was detected in 18 of 31 patients. Bone lesions were seen in 16 of the 18 MIP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 10 publications
1
56
1
5
Order By: Relevance
“…PTH does not have a primary role in MM bone disease. PTH levels of MM patients have been found to be similar to those in healthy controls, however, a few hypercalcemic MM patients were reported to have had high levels of PTH related peptide, which may cause hypercalcemia [35][36][37].…”
Section: Discussionmentioning
confidence: 98%
“…PTH does not have a primary role in MM bone disease. PTH levels of MM patients have been found to be similar to those in healthy controls, however, a few hypercalcemic MM patients were reported to have had high levels of PTH related peptide, which may cause hypercalcemia [35][36][37].…”
Section: Discussionmentioning
confidence: 98%
“…It strongly correlates with osteolytic burden in MM [57][58][59]. Indeed, CCL3 by binding two receptors, CCR1 and CCR5, potently stimulates OC differentiation mediating the fusion of precursor cells into active mature OCs and upregulating RANKL expression by OBs [60][61][62].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…Recently, the genes that encode for macrophage inflammatory protein-1 alpha (MIP-1a) and -beta (MIP-1b) (CCL3 and CCL4 respectively) have been identified as candidate genes for osteclastogenic factors (Choi et al, 2000;Han et al, 2001;Abe et al, 2002) and studies have shown that the majority of MM cells from patients and MM cell lines secrete MIP-1a and MIP1b (Abe et al, 2002;Uneda et al, 2003;Hashimoto et al, 2004) and serum MIP-1a levels correlate with the extent of OBD and survival (Terpos et al, 2005). These factors enhance osteoclast formation by binding to their cognate receptor, CCR5, on osteoclast precursors.…”
mentioning
confidence: 99%